The mathematical olympiad handbook : An introduction to problem solving - Gardiner, A. (New York : Oxford University press, 2000)
Olympiad problems help able secondary pupils develop their mathematical muscles. Good Olympiad problems are unpredictable: this makes them worthwhile, but it also makes them seem hard - even unapproachable. The Mathematical Olympiad Handbook contains some of the Mathematical Olympiads 1965-1996 in a form designed to help bright students overcome this barrier
Keywords: Mathematics -- Problems, exercises, etc